Identification and Characterization of Marine Debris on Teluk Penyu Beach, Cilacap - Lady Ayu Sri Wijayanti; Gilar Budi Pratama; Andini N.A.; Raziq Aldin; Ismail Maqbul; Mochamad Ramdhan Firdaus (Sam Ratulangi University, 2025)
This study was conducted at Teluk Penyu Beach, Cilacap Regency, with the aim of analyzing the composition, density, and primary sources of marine debris in the area. Sampling was carried out from October to November 2024 using a 5×5 m quadrat transect method along the shoreline, with a 20 m distance between transects. The results showed that a total of 2,021 debris pieces were collected, with the main composition consisting of wood debris (1,485 pieces; 62.80%), plastic (469 pieces; 19%), other materials (294 pieces; 14.58%), plastic foam (42 pieces; 2.60%), fabric (10 pieces; 1.12%), and rubber (7 pieces; 0.17%). The highest debris density was found in the wood category, with 12 pieces/m², followed by plastic (3.752 pieces/m²), plastic foam (0.336 pieces/m²), other materials (0.16 pieces/m²), fabric (0.133 pieces/m²), and rubber (0.14 pieces/m²). Based on the Clean-Coast Index (CCI) calculation, the beach cleanliness index score of 8 indicates that Teluk Penyu Beach falls into the